Parent mental health and child behavior during the COVID-19 pandemic. (May 2023) - Scheiber, Francesca; Nelson, Paige M.; Momany, Allison; Ryckman, Kelli K.; Ece Demir-Lira, Ö.
Highlights: Parental depression symptoms increased during the pandemic. Parental well-being decreased during the pandemic. Child internalizing and externalizing symptoms increased during the pandemic. Change in parental depression symptoms was associated with change in child behavior. Prematurity did not moderate relations between parent mental health and child behavior. Abstract: Objective: Child behavior, which encompasses both internalizing and externalizing behaviors, is associated with many outcomes, including concurrent and future mental health, academic success, and social well-being. Thus, understanding sources of variability in child behavior is crucial for developing strategies aimed at equipping children with necessary resources. Parental mental health (PMH) difficulties and preterm birth may be risk factors for child behavior (CB) problems. Moreover, not only are PMH difficulties more common among parents of preterm children, but preterm children might also be more sensitive than full-term children to environmental stressors. In this study, we examined how PMH and CB changed during the COVID-19 pandemic, how change in PMH related to change in CB, and whether preterm children were more susceptible than full-term children to change in PMH. Methods: Parents that participated in a study prior to the pandemic were invited to complete follow-up questionnaires during the pandemic about PMH and CB. Forty-eight parents completed follow-up questionnaires. Results: Our results suggested that parental depression symptoms, children's internalizing symptoms, and children's externalizing symptoms significantly increased, and parental well-being significantly decreased during the pandemic. Change in parental depression symptoms, but not change in parental anxiety symptoms or parental well-being, was associated with change in children's internalizing and externalizing symptoms. Prematurity did not moderate change in PMH, change in CB, or the effect of change in PMH on change in CB. Conclusion: Our findings have the potential to inform efforts aimed at equipping children with behavioral resources.